Activation of alpha-Fe2O3 for Photoelectrochemical Water Splitting Strongly Enhanced by Low Temperature Annealing in Low Oxygen Containing Ambient - Makimizu, Yoichi; Nguyen, Nhat Truong; Tucek, Jiri; Ahn, Hyo-Jin; Yoo, Jeong Eun; Poornajar, Mahshid; Hwang, Imgon; Kment, Stepan; Schmuki, Patrik (Chemistry - A European Journal, 2020)
Photoelectrochemical (PEC) water splitting is a promising method for the conversion of solar energy into chemical energy stored in the form of hydrogen. Nanostructured hematite (alpha-Fe2O3) is one of the most attractive materials for a highly efficient charge carrier generation and collection due to its large specific surface area and the short minority carrier diffusion length. In the present work, the PEC water splitting performance of nanostructured alpha-Fe2O3 is investigated which was prepared by anodization followed by annealing in a low oxygen ambient (0.03 % O-2 in Ar). It was found that low oxygen annealing can activate a significant PEC response of alpha-Fe2O3 even at a low temperature of 400 degrees C and provide an excellent PEC performance compared with classic air annealing. The photocurrent of the alpha-Fe2O3 annealed in the low oxygen at 1.5 V vs. RHE results as 0.5 mA cm(-2), being 20 times higher than that of annealing in air. The obtained results show that the alpha-Fe2O3 annealed in low oxygen contains beneficial defects and promotes the transport of holes; it can be attributed to the improvement of conductivity due to the introduction of suitable oxygen vacancies in the alpha-Fe2O3. Additionally, we demonstrate the photocurrent of alpha-Fe2O3 annealed in low oxygen ambient can be further enhanced by Zn-Co LDH, which is a co-catalyst of oxygen evolution reaction. This indicates low oxygen annealing generates a promising method to obtain an excellent PEC water splitting performance from alpha-Fe2O3 photoanodes.
CRIS-Team WoS Importer:2020-02-21

A High-Field Anodic NiO Nanosponge with Tunable Thickness for Application in p-Type Dye-Sensitized Solar Cells - Sultan, Umair; Ahmadloo, Farzaneh; Cha, Gi; Gökcan, Baris; Hejazi, Seyedsina; Yoo, Jeong Eun; Nguyen, Nhat Truong; Altomare, Marco; Schmuki, Patrik; Killian, Manuela (ACS Applied Energy Materials, 2020)
Dye-sensitized photocathodes have the potential to significantly contribute to the efficiency of the solar light-to-current conversion in tandem dye-sensitized solar cells (DSSCs). A novel, highly porous nanoarchitecture of NiO is developed in this project. The spongelike material is grown by anodization, shows a virtually crack-free morphology, strongly adheres to the substrate, and can be grown with a controllable thickness of at least up to 6.5 mu m. The oxide composition is NiO and the nanosponge exhibits p-type semiconductive behavior. A doubling of the maximum reported p-type DSSC efficiency compared to coumarin C343-sensitized NiO nanoparticle photocathodes can be achieved with the NiO nanosponge. The developed dye-sensitized p-type NiO-based cathodes are promising for application as photocathodes in tandem DSSC devices.
CRIS-Team WoS Importer:2020-09-18

Amorphous Mo-Ta Oxide Nanotubes for Long-Term Stable Mo Oxide-Based Supercapacitors - Jin, Bowen; Hejazi, Seyedsina; Pyczak, Florian; Oehring, Michael; Mohajernia, Shiva; Kment, Stepan; Tomanec, Ondrej; Zboril, Radek; Nguyen, Nhat Truong; Yang, Min; Schmuki, Patrik (ACS Applied Materials and Interfaces, 2019)
With a large-scale usage of portable electric appliances, a high demand for increasingly high-density energy storage devices has emerged. MoO3 has, in principle, a large potential as a negative electrode material in supercapacitive devices due to high charge densities that can be obtained from its reversible redox reactions. Nevertheless, the extremely poor electrochemical stability of MoO3 in aqueous electrolytes prevents a practical use in high capacitance devices. In this work, we describe how to overcome this severe stability issue by forming amorphous molybdenum oxide/tantalum oxide nanotubes by anodic oxidation of a Mo-Ta alloy. The presence of a critical amount of Ta oxide (>20 at. %) prevents the electrochemical decay of the MoO3 phase and thus yields an extremely high stability. Due to the protection provided by tantalum oxide, no capacitance losses are measureable after 10,000 charging/discharging cycles.
CRIS-Team Scopus Importer:2019-12-10
Keywords: cycle stability; Mo oxide; nanotubes; supercapacitor; Ta oxide

Anodic TiO2 nanotube layers: Why does self-organized growth occur-A mini review - Zhou, Xuemei; Nguyen, Nhat Truong; Özkan, Selda; Schmuki, Patrik (Electrochemistry Communications, 2014)
The present review gives an overview of the highlights of more than 10 years of research on synthesis and applications of ordered oxide structures (nanotube layers, hexagonal pore arrangements) that are formed by self-organizing anodization of metals. In particular we address the questions after the critical factors that lead to the spectacular self-ordering during the growth of anodic oxides that finally yield morphologies such as highly ordered TiO2 nanotube arrays and similar structures. Why are tubes and pores formed-what are the key parameters controlling these processes?
EAM Import::2019-03-13

Anodic Titanium Dioxide Nanotubes for Magnetically Guided Therapeutic Delivery - Hasanzadeh Kafshgari, Morteza; Kah, Delf-Thorge Eric; Mazare, Anca Valentina; Nguyen, Nhat Truong; Distaso, Monica; Peukert, Wolfgang; Goldmann, Wolfgang; Schmuki, Patrik; Fabry, Ben (Scientific Reports, 2019)
Hollow titanium dioxide (TiO2) nanotubes offer substantially higher drug loading capacity and slower drug release kinetics compared to solid drug nanocarriers of comparable size. In this report, we load TiO2 nanotubes with iron oxide nanoparticles to facilitate site-specific magnetic guidance and drug delivery. We generate magnetic TiO2 nanotubes (TiO2NTs) by incorporating a ferrofluid containing Ø ≈ 10 nm iron oxide nanoparticles in planar sheets of weakly connected TiO2 nanotubes. After thermal annealing, the magnetic tubular arrays are loaded with therapeutic drugs and then sonicated to separate the nanotubes. We demonstrate that magnetic TiO2NTs are non-toxic for HeLa cells at therapeutic concentrations (≤200 µg/mL). Adhesion and endocytosis of magnetic nanotubes to a layer of HeLa cells are increased in the presence of a magnetic gradient field. As a proof-of-concept, we load the nanotubes with the topoisomerase inhibitor camptothecin and achieve a 90% killing efficiency. We also load the nanotubes with oligonucleotides for cell transfection and achieve 100% cellular uptake efficiency. Our results demonstrate the potential of magnetic TiO2NTs for a wide range of biomedical applications, including site-specific delivery of therapeutic drugs.
CRIS-Team Scopus Importer:2019-09-27

Black Magic in Gray Titania: Noble-Metal-Free Photocatalytic H2 Evolution from Hydrogenated Anatase - Liu, Ning; Zhou, Xuemei; Nguyen, Nhat Truong; Peters, Kristina; Zoller, Florian; Hwang, Imgon; Schneider, Christopher; Miehlich, Matthias; Freitag, Detlef; Meyer, Karsten; Fattakhova-Rohlfing, Dina; Schmuki, Patrik (Chemsuschem, 2017)
‘Black’ TiO2—in the widest sense, TiO2reduced by various treatments—has attracted tremendous scientific interest in recent years because of some outstanding properties; most remarkably in photocatalysis. While the material effects visible light absorption (the blacker, the better), black titania produced by high pressure hydrogenation was recently reported to show another highly interesting feature; noble-metal-free photocatalytic H2generation. In a systematic investigation of high-temperature hydrogen treatments of anatase nanoparticles, TEM, XRD, EPR, XPS, and photoelectrochemistry are used to characterize different degrees of surface hydrogenation, surface termination, electrical conductivity, and structural defects in the differently treated materials. The materials’ intrinsic activity for photocatalytic hydrogen evolution is coupled neither with their visible light absorption behavior nor the formation of amorphous material, but rather must be ascribed to optimized and specific defect formation (gray is better than black). This finding is further confirmed by using a mesoporous anatase matrix as a hydrogenation precursor, which, after conversion to the gray state, even further enhances the overall photocatalytic hydrogen evolution activity.
CRIS-Team Scopus Importer:2020-09-14
Keywords: absorption; hydrogen evolution; hydrogenation; photocatalysis; titania

Dewetted Au Nanoparticles on TiO2 Surfaces: Evidence of a Size-Independent Plasmonic Photoelectrochemical Response - Licklederer, Markus; Mohammadi, Reza; Nguyen, Nhat Truong; Park, Hyoungwon; Hejazi, Seyedsina; Halik, Marcus; Vogel, Nicolas; Altomare, Marco; Schmuki, Patrik (Journal of Physical Chemistry C, 2019)
We induce solid-state dewetting of thin Au films (nominal thickness of 0.5-10 nm) on flat TiO2 surfaces to produce Au nanoparticles with an average size tunable in the 3-200 nm range. Such Au-decorated TiO2 surfaces enable plasmonic photoelectrochemical water splitting under visible light illumination (450-750 nm), with a photon-to-current conversion efficiency that reaches a maximum for TiO2 surfaces decorated with similar to 30 nm sized Au particles. Optical measurements show, as expected, a red shift of the plasmon resonance with the increasing Au nanoparticle size. More interestingly, the photocurrent is found to peak for every photoanode at similar to 600 nm regardless of the Au nanoparticle size, i.e., the wavelength of maximum photocurrent is size-independent. Such a remarkable observation can be ascribed to a hot electron injection cutoff effect, i.e., can be explained in terms of the interband versus intraband transition scenario.
CRIS-Team WoS Importer:2019-07-30

Effects of low oxygen annealing on the photoelectrochemical water splitting properties of α-Fe2O3 - Makimizu, Yoichi; Yoo, Jeong Eun; Poornajar, Mahshid; Nguyen, Nhat Truong; Ahn, Hyo-Jin; Hwang, Imgon; Kment, Stepan; Schmuki, Patrik (Journal of Materials Chemistry A, 2020)
Photoelectrochemical (PEC) water splitting is a promising method for converting solar energy into chemical energy stored in the form of hydrogen. Nanostructured hematite (α-Fe2O3) is one of the most attractive materials for highly efficient charge carrier generation and collection, due to its large specific surface area and shortened minority carrier diffusion length required to reach the surface. In the present work, PEC water splitting performance of α-Fe2O3 prepared by anodization of thin iron layers on FTO glass and subsequent annealing in a low O2-Ar atmosphere with only 0.03% O2 was investigated. The key finding is that annealing anodic nanostructures with a low oxygen concentration provides a strongly enhanced PEC performance compared with classical air annealing. The photocurrent of the former at 1.5 V vs. RHE results in 1.1 mA cm-2, being 11 times higher than that of the latter. The enhancement of the PEC performance of α-Fe2O3 annealed in a low oxygen atmosphere can be attributed to the controlled morphology, Sn doping, and introduction of oxygen vacancies, which contribute to the enhancement of the hole flux from the photogenerated site to the reactive surface and additionally lead to an enhanced hole transfer at the interface between α-Fe2O3 and the electrolyte. From the obtained results, it is evident that low oxygen annealing is a surprisingly effective method of defect engineering and optimizing α-Fe2O3 electrodes for a maximized PEC water splitting performance.
CRIS-Team Scopus Importer:2020-02-07

Efficient Photocatalytic H2 Evolution: Controlled Dewetting-Dealloying to Fabricate Site-Selective High-Activity Nanoporous Au Particles on Highly Ordered TiO2 Nanotube Arrays - Nguyen, Nhat Truong; Altomare, Marco; Yoo, Jeong Eun; Schmuki, Patrik (Advanced Materials, 2015)
Anodic self-organized TiO2 nanostumps are formed and exploited for self-ordering dewetting of Au–Ag sputtered films. This forms ordered particle configurations at the tube top (crown position) or bottom (ground position). By dealloying from a minimal amount of noble metal, porous Au nanoparticles are then formed, which, when in the crown position, allow for a drastically improved photocatalytic H2 production compared with nanoparticles produced by conventional dewetting processes.
EAM Import::2019-03-14

Fe2O3 Blocking Layer Produced by Cyclic Voltammetry Leads to Improved Photoelectrochemical Performance of Hematite Nanorods - Poornajar, Mahshid; Nguyen, Nhat Truong; Ahn, Hyo-Jin; Buechler, Markus; Liu, Ning; Kment, Stepan; Zbořil, Radek; Yoo, Jeong Eun; Schmuki, Patrik (Surfaces, 2019)
Hematite is a low band gap, earth abundant semiconductor and it is considered to be a promising choice for photoelectrochemical water splitting. However, as a bulk material its efficiency is low because of excessive bulk, surface, and interface recombination. In the present work, we propose a strategy to prepare a hematite (alpha -Fe2O3) photoanode consisting of hematite nanorods grown onto an iron oxide blocking layer. This blocking layer is formed from a sputter deposited thin metallic iron film on fluorine doped tin oxide (FTO) by using cyclic voltammetry to fully convert the film into an anodic oxide. In a second step, hematite nanorods (NR) are grown onto the layer using a hydrothermal approach. In this geometry, the hematite sub-layer works as a barrier for electron back diffusion (a blocking layer). This suppresses recombination, and the maximum of the incident photon to current efficiency is increased from 12% to 17%. Under AM 1.5 conditions, the photocurrent density reaches approximately 1.2 mA/cm(2) at 1.5 V vs. RHE and the onset potential changes to 0.8 V vs. RHE (using a Zn-Co co-catalyst).
CRIS-Team WoS Importer:2021-10-18

Forming a Highly Active, Homogeneously Alloyed AuPt Co-catalyst Decoration on TiO2 Nanotubes Directly during Anodic Growth - Bian, Haidong; Nguyen, Nhat Truong; Yoo, Jeong Eun; Hejazi, Seyedsina; Mohajernia, Shiva; Müller, Julian; Spiecker, Erdmann; Tsuchiya, Hiroaki; Tomanec, Ondrej; Sanabria Arenas, Beatriz Eugenia; Zboril, Radek; Li, Yang Yang; et al. (ACS Applied Materials and Interfaces, 2018)
Au and Pt do not form homogeneous bulk alloys as they are thermodynamically not miscible. However, we show that anodic TiO2 nanotubes (NTs) can in-situ be uniformly decorated with homogeneous AuPt alloy nanoparticles (NPs) during their anodic growth. For this, a metallic Ti substrate containing low amounts of dissolved Au (0.1 at%) and Pt (0.1 at%) is used for anodizing. The matrix metal (Ti) is converted to oxide while at the oxide/metal interface direct noble metal particle formation and alloying of Au and Pt takes place; continuously these particles are then picked up by the growing nanotube wall. In our experiments the AuPt alloy NPs have an average size of 4.2 nm and, at the end of the anodic process, are regularly dispersed over the TiO2 nanotubes. These alloyed AuPt particles act as excellent co-catalyst in photocatalytic H2 generation - with a H2 production of 12.04 μL h-1 under solar light. This represents a strongly enhanced activity as compared with TiO2 NTs decorated with monometallic particles of Au (7 μL h-1) or Pt (9.96 μL h-1)
Keywords: anodization; photocatalysis; TiO2 nanotubes; AuPt alloy nanoparticle; H2 evolution

Hierarchical decoration of anodic TiO2 nanorods for enhanced photocatalytic degradation properties - Tsui, Lok-Kun; Nguyen, Nhat Truong; Wang, Lei; Kirchgeorg, Robin; Zangari, Giovanni; Schmuki, Patrik (Electrochimica Acta, 2015)
In the present work vertically aligned TiO2 nanorods were fabricated by anodization of Al/Ti dual layer structures. Anodization of Al leads to the formation of a porous alumina layer which is used as a template for the growth of TiO2 nanorods. We have studied the characteristics of these nanorods after annealing by high resolution TEM, showing a core–shell structure along the length of the nanorods formed from the expansion of the TiO2 nanorod into the alumina template during growth. Modification of the nanorods by spin coating of a solution of titanium isopropoxide (TIPO) in isopropanol yields enhanced photocatalytic activity up to 12 times due to the increase in surface area, light absorption volume, and the creation of a crystalline coating with an anatase-phase.
EAM Import::2019-03-13

High temperature oxidation behaviour of AISI 321 stainless steel with an ultrafine-grained surface at 800 °C in Ar–20 vol.% O2 - Pour-Ali, Sadegh; Weiser, Martin; Nguyen, Nhat Truong; Kiani-Rashid, Ali Reza; Babakhani, Abolfazl; Virtanen, Sannakaisa (Corrosion Science, 2019)
Oxidation behaviour of surface nanocrystallized 321 austenitic stainless steel (SN–321ASS) and its conventional polycrystalline counterpart (CP–321ASS) in Ar + 20% O2 at 800 °C is comparatively investigated. Severe breakaway oxidation sets in for the CP–321ASS after 100 h, while the SN–321ASS shows a higher oxidation resistance. Surface nanocrystallization increases the diffusion and flux of Cr towards the oxidation front, and can consequently promote the kinetics of early oxidation and accelerate the formation of a thicker Cr-rich inner oxide layer, which aids in prohibiting the enhanced formation of Fe-rich oxides.
CRIS-Team Scopus Importer:2019-10-29
Keywords: A. Stainless steel; B. TEM; B. XRD; C. Oxidation

Intrinsic Au-decoration on anodic TiO2 nanotubes grown from metastable Ti-Au sputtered alloys-High density co-catalyst decoration enhances the photocatalytic H-2 evolution - Hejazi, Seyedsina; Altomare, Marco; Nguyen, Nhat Truong; Mohajernia, Shiva; Licklederer, Markus; Schmuki, Patrik (Applied Materials Today, 2019)
Recent work demonstrated that intrinsic Au nanoparticle decoration of TiO2 nanotube arrays (NTs) can be achieved by electrochemical anodization of Ti-Au alloy substrates. However, for a Ti-Au cast alloy produced by melt-alloying, the Au concentration cannot exceed the solubility limit of Au in Ti of 0.2 at.% - this sets constraints on the intrinsic Au nanoparticle loading on anodic TiO2 NTs. Here we explore "metastable" Ti-Au metal substrates that are produced by Ti and Au cosputtering and we establish Au concentrations that far exceed the solubility limit in cast Ti-Au alloys. We show the use of these "metastable" Ti-Au sputtered layers for the anodic formation of TiO2 NTs with a much higher density of Au nanoparticle loading than using classic alloys. Under optimized conditions (Au nanoparticle density) photocatalytic H-2 production from such Au@TiO2 platforms provides a 15 times higher photocatalytic H-2 evolution rate than the best rates achieved with conventional alloys. (C) 2018 Elsevier Ltd. All rights reserved.
CRIS-Team WoS Importer:2019-02-27

Li+ Pre-Insertion Leads to Formation of Solid Electrolyte Interface on TiO2 Nanotubes That Enables High-Performance Anodes for Sodium Ion Batteries - Cha, Gi; Mohajernia, Shiva; Nguyen, Nhat Truong; Mazare, Anca Valentina; Denisov, Nikita; Hwang, Imgon; Schmuki, Patrik (Advanced Energy Materials, 2019)
Recently, sodium ion batteries (SIBs) have been widely investigated as one of the most promising candidates for replacing lithium ion batteries (LIBs). For SIBs or LIBs, designing a stable and uniform solid electrolyte interphase (SEI) at the electrode–electrolyte interface is the key factor to provide high capacity, long-term cycling, and high-rate performance. In this paper, it is described how a remarkably enhanced SEI layer can be obtained on TiO2 nanotube (TiO2 NTs) arrays that allows for a strongly improved performance of sodium battery systems. Key is that a Li+ pre-insertion in TiO2 NTs can condition the SEI for Na+ replacement. SIBs constructed with Li-pre-inserted NTs deliver an exceptional Na+ cycling stability (e.g., 99.9 ± 0.1% capacity retention during 250 cycles at a current rate of 50 mA g−1) and an excellent rate capability (e.g., 132 mA h g−1 at a current rate of 1 A g−1). The key factor in this outstanding performance is that Li-pre-insertion into TiO2 NTs leads not only to an enhanced electronic conductivity in the tubes, but also expands the anatase lattice for facilitated subsequent Na+ cycling.
CRIS-Team Scopus Importer:2019-12-31
Keywords: anodization; pre-lithiation; sodium ion batteries; solid electrolyte interphases; TiO

Long-Living Holes in Grey Anatase TiO2 Enable Noble-Metal-Free and Sacrificial-Agent-Free Water Splitting - Liu, Ning; Mohajernia, Shiva; Nguyen, Nhat Truong; Hejazi, Seyedsina; Plass, Fabian; Kahnt, Axel; Yokosawa, Tadahiro; Osvet, Andres; Spiecker, Erdmann; Guldi, Dirk Michael; Schmuki, Patrik (Chemsuschem, 2020)
Titanium dioxide has been the benchmark semiconductor in photocatalysis for more than 40 years. Full water splitting, that is, decomposing water into H2 and O2 in stoichiometric amounts and with an acceptable activity, still remains a challenge, even when TiO2-based photocatalysts are used in combination with noble-metal co-catalysts. The bottleneck of anatase-type TiO2 remains the water oxidation, that is, the hole transfer reaction from pristine anatase to the aqueous environment. In this work, we report that “grey” (defect engineered) anatase can provide a drastically enhanced lifetime of photogenerated holes, which, in turn, enables an efficient oxidation reaction of water to peroxide via a two-electron pathway. As a result, a Ni@grey anatase TiO2 catalyst can be constructed with an impressive performance in terms of photocatalytic splitting of neutral water into H2 and a stoichiometric amount of H2O2 without the need of any noble metals or sacrificial agents. The finding of long hole lifetimes in grey anatase opens up a wide spectrum of further photocatalytic applications of this material.
CRIS-Team Scopus Importer:2020-08-21
Keywords: long-living holes; noble-metal-free; sacrificial-agent-free; titanium dioxide; water splitting

Magnetite-Free Sn-Doped Hematite Nanoflake Layers for Enhanced Photoelectrochemical Water Splitting - Ahn, Hyo-Jin; Kment, Stepan; Yoo, Jeong Eun; Nguyen, Nhat Truong; Naldoni, Alberto; Zboril, Radek; Schmuki, Patrik (ChemElectroChem, 2022)
In the present work, we report a preparation strategy for hematite phase-pure photoanodes consisting of Sn-doped hematite nanoflakes/hematite thin film bilayer nanostructure (Sn-HB). This approach is based on a two-step annealing process of pure iron films deposited on fluorine doped tin oxide (FTO) substrates by advanced magnetron sputtering. While the high density hematite ultrathin nanoflakes (HNs) with detrimental iron oxide layers (Fe3O4 and/or FeO) are generated during the first annealing step at 400 degrees C for two hours, the second thermal treatment at 800 degrees C for 15 minutes oxidises all the undesired iron oxide phases to a photoactive hematite layer as well as is providing efficient Sn doping of a drop-casted SnCl4 in order to increase the conductivity. The optimized Sn-HB shows an around 11 times higher photocurrent density (0.71 mA cm(-2) at 1.23 V-RHE) compared with a reference hematite photoanode produced from iron foil under the same conditions.
CRIS-Team WoS Importer:2022-06-17

MoP-protected Mo oxide nanotube arrays for long-term stable supercapacitors - Bowen, Jin; Hejazi, Seyedsina; Hongqi, Chu; Mohajernia, Shiva; Nguyen, Nhat Truong; Min, Yang; Altomare, Marco; Schmuki, Patrik (Applied Materials Today, 2019)
In the current energy scenario, electrochemical capacitors hold the promise to fulfil requirements of high power densities, short charging-discharging times, and long lifetimes. For such supercapacitors, MoO3 is one of the most potent candidate as a negative electrode material, due to a very high theoretical charge density ascribed to easily-switchable multiple oxidation states. Nevertheless, the extremely poor electrochemical stability of MoO3 in aqueous electrolytes prevents any practical use. In the present work, we outline a strategy to overcome the poor stability of MoO3 electrodes: we produce by thermal phosphidation an amorphous MoP protective shell on Mo oxide nanotube arrays. This not only leads to an outstanding stability of the electrode but the phosphidized hybrid structures even maintains a capacitance as high as the initial capacitance (i.e. measured before deterioration) of unprotected pure oxide structures: the phosphidized hybrid structure, used as binder-free electrodes, can deliver a non-intercalation-based volumetric capacitance of over 2000 F cm−3 with an outstanding capacitance retention of ∼93% over 10,000 charging/discharging cycles.
CRIS-Team Scopus Importer:2019-09-17
Keywords: Electrochemical stability; Mo oxide; MoP; Nanotubes; Supercapacitor; Volumetric capacitance

Noble Metals on Anodic TiO2 Nanotube Mouths: Thermal Dewetting of Minimal Pt Co-Catalyst Loading Leads to Significantly Enhanced Photocatalytic H2 Generation - Nguyen, Nhat Truong; Altomare, Marco; Yoo, Jeong Eun; Taccardi, Nicola; Schmuki, Patrik (Advanced Energy Materials, 2016)
A technique is introduced to strongly reduce Pt use for photocatalytic hydrogen generation from TiO2 nanotubes. By site selectively depositing thin layers of Pt only at the ``mouth'' of the nanotubes, and with a subsequent thermal dewetting step, an outstanding photocatalytic improvement with minimal amounts of cocatalyst is achieved.
EAM Import::2019-03-08

On the material characteristics of a high carbon cast austenitic stainless steel after solution annealing followed by quenching in a CNT nanofluid - Pour-Ali, Sadegh; Kiani-Rashid, Ali-Reza; Babakhani, Abolfazl; Virtanen, Sannakaisa; Nguyen, Nhat Truong; Hejazi, Seyedsina; Davoodi, Ali; Nazarnejatizadeh, Afshin; Teimourinejad, Hashem (International Journal of Materials Research, 2019)
Solution annealing followed by quenching in carbon nanotubes (QCNT) nanofluid treatment was applied to generate very high interstitial carbon content, approximate to 0.30 wt.%, in an austenitic stainless steel (ASS). The high interstitial carbon content leads to remarkable improvement in mechanical properties with essentially no loss of ductility, with no chromium carbides and/or martensite formation. To evaluate the localized corrosion tendency and passivity behavior, 3.5 wt.% NaCl and borate buffer solutions were used, respectively. Based on the electrochemical corrosion results, both high carbon and low carbon (0.030 wt.%) QCNT-treated ASS alloys show comparable passivity and localized corrosion performance. In addition, Mott-Schottky plots revealed that the anodic films on QCNT-treated samples exhibit similar semiconducting characters.
CRIS-Team WoS Importer:2019-06-28

Providing significantly enhanced photocatalytic H2 generation using porous PtPdAg alloy nanoparticles on spaced TiO2 nanotubes - Nguyen, Nhat Truong; Ozkan, S.; Hejazi, Seyedsina; Denisov, Nikita; Tomanec, Ondrej; Zboril, R.; Schmuki, Patrik (International Journal of Hydrogen Energy, 2019)
In the present work we introduce a simple approach to produce porous PtPdAg alloy nanoparticles on TiO2 nanotubes by a simple combined sputtering-dewetting-dealloying process. In a first step, three individual metals (Pt, Pd and Ag) were sequentially sputter-deposited on spaced TiO2 nanotubes, followed by a thermal dewetting treatment in Ar to convert these metal layers into ternary PtPdAg alloyed particles. Dealloying was carried out by a selective chemical dissolution of Ag in piranha solution that finally generated porous alloyed nanoparticles located on the TiO2 nanotube walls. The porous PtPdAg-decorated TiO2 nanotubes show enhanced photocatalytic H2 generation in comparison with porous Pt (67% increase) or any monometallic decoration (>120% increase). The photocatalytic enhancement is not only due to the increased number of active sites (larger surface area) of the porous particles but also due to the synergistic effects of the different alloying elements.
CRIS-Team Scopus Importer:2019-08-02
Keywords: Dealloying; Dewetting; Photocatalytic H; PtPd alloy; TiO

Stable Co-Catalyst-Free Photocatalytic H 2 Evolution From Oxidized Titanium Nitride Nanopowders - Zhou, Xuemei; Zolnhofer, Eva; Nguyen, Nhat Truong; Liu, Ning; Meyer, Karsten; Schmuki, Patrik (Angewandte Chemie, 2015)
A simple strategy is used to thermally oxidize TiN nanopowder (∼20nm) to an anatase phase of a TiO2:Ti3+:N compound. In contrast to the rutile phase of such a compound, this photocatalyst provides activity for hydrogen evolution under AM1.5 conditions, without the use of any noble metal co-catalyst. Moreover the photocatalyst is active and stable over extended periods of time (tested for 4months). Importantly, to achieve successful conversion to the active anatase polymorph, sufficiently small starting particles of TiN are needed. The key factor for catalysis is the stabilization of the co-catalytically active Ti3+ species against oxidation by nitrogen present in the starting material.
EAM Import::2019-03-13

'Suspended' Pt nanoparticles over TiO2 nanotubes for enhanced photocatalytic H2 evolution - Nguyen, Nhat Truong; Yoo, Jeong Eun; Altomarea, Marco; Schmuki, Patrik (Chemical Communications, 2014)
In the present work we introduce a technique to form a photocatalyst based on Pt nanoparticles suspended over the mouth of anodic TiO2 nanotubes. These structures are obtained by decorating the top end of highly ordered TiO2 nanotubes with a web of TiO2 nanofibrils, followed by sputter deposition of a minimum amount of Pt. A subsequent thermal dewetting step forms 3–6 nm-sized Pt nanoparticles along the nanofibrils. These structures, when compared to conventional Pt decoration techniques of TiO2 nanotubes, show strongly enhanced photocatalytic H2 evolution efficiency.
EAM Import::2019-03-12

Tantalum Nitride Nanorod Arrays: Introducing Ni–Fe Layered Double Hydroxides as a Cocatalyst Strongly Stabilizing Photoanodes in Water Splitting - Wang, Lei; Dionigi, Fabio; Nguyen, Nhat Truong; Kirchgeorg, Robin; Gliech, Manuel; Grigorescu, Sabina Georgiana; Strasser, Peter; Schmuki, Patrik (Chemistry of Materials, 2015)
Ta3N5 nanostructures are widely explored as anodes for photoelectrochemical (PEC) water splitting. Although the material shows excellent semiconductive properties for this purpose, the key challenge is its severe photocorrosion when used in typical aqueous environments. In the present work we introduce a NiFe layered double hydroxide (LDH) cocatalyst that dramatically reduces photocorrosion effects. To fabricate the Ta3N5 electrode, we use through-template anodization of Ta and obtain oxide nanorod arrays that then are converted to Ta3N5 by high temperature nitridation. After modification with our cocatalyst system, we obtained solar photocurrents of 6.3 mA cm–2 at 1.23 VRHE in 1 M KOH, and an electrode maintains about 80% of the initial activity for extended irradiation times.
EAM Import::2019-03-12

TiO2 Nanotubes: Nitrogen-Ion Implantation at Low Dose Provides Noble-Metal-Free Photocatalytic H-2-Evolution Activity - Zhou, Xuemei; Häublein, Volker; Liu, Ning; Nguyen, Nhat Truong; Zolnhofer, Eva; Tsuchiya, Hiroaki; Manuela, Killian; Meyer, Karsten; Schmuki, Patrik; Frey, Lothar (Angewandte Chemie International Edition, 2016)
Low-dose nitrogen implantation induces an ion and damage profile in TiO2 nanotubes that leads to co-catalytic activity for photocatalytic H-2-evolution (without the use of any noble metal). Ion implantation with adequate parameters creates this active zone limited to the top part of the tubes. The coupling of this top layer and the underlying non-implanted part of the nanotubes additionally contributes to an efficient carrier separation and thus to a significantly enhanced H-2 generatio
Keywords: H-2 evolution; ion implantation; nitrogen; photocatalysis; TiO2 nanotubes

Use of Anodic TiO2 Nanotube Layers as Mesoporous Scaffolds for Fabricating CH3NH3Pbl3 Perovskite-Based Solid-State Solar Cells - Salazar, Raul; Altomare, Marco; Lee, Kiyoung; Tripathy, Jyotsna; Kirchgeorg, Robin; Nguyen, Nhat Truong; Mokhtar, Mohamed; Alshehri, Abdelmohsen; Al-Thabaiti, Shaeel A.; Schmuki, Patrik (ChemElectroChem, 2015)
We optimize the deposition of CH3NH3PbI3 perovskite into mesoporous electrodes consisting of anodic TiO2 nanotube layers. By a simple spin-coating approach, complete filling of the tube scaffolds is obtained, which leads to interdigitated perovskite structures in conformal contact with the TiO2 tube counterparts. Such assemblies can be used as solid-state solar cells in a hole-transporting-material-free configuration, that is, the tube scaffold serves as electron collector and blocking layer, while the perovskite acts as visible-light absorber and hole-transporting material. We show that the complete filling of the tube scaffold with the perovskite is essential to improve the solar cell efficiency.
EAM Import::2019-03-12